To Identify the Causes of Stress among Nurses Working in Intensive Care Unit of Ittefaq Hospital Lahore - Johan, Salma; Sarwar, Hajra; Majeed, Iram (International Journal of Social Sciences and Management, 2017)
The study is aimed at identifying the causes of stress amongst daily routine of nurses working in the ICU unit of Ittefaq Hospital Lahore. A questionnaire was developed and distributed to gain an insight into factors which may be causing stress to the nurses. The results were analyzed using statistical tools. An overall finding of the study is that all the nurses were suffering from stress however, the reasons of stress are different. Consensus was that three biggest causes of stress are prolonged shifts and extra duties, shortage of staff and excessive workload. The other major causes of stress identified are inappropriate or poor communication between doctors and nurses, lack of support and motivation, unexpected deaths or patients undergoing painful procedures, lack of breaks, lack of cooperation from peers and supervisors/managers. The patients themselves can also be a source of stress for example, problematic patients or their aggressive family members as well as improper work environment also contribute to stress. There is a dire need to develop stress alleviating programs and therapies at the hospitals. Nurses, doctors and managers should be encouraged to participate in such programs towards building stress-free work environment where patients can be served better. Int. J. Soc. Sc. Manage. Vol. 4, Issue-2: 96-109